Improving Students’ Reading Skills through Jeopardy Games - I Gusti Ayu Agung Werdiyani (English Education Department STKIP Agama Hindu Singaraja, 2021)
This study is a literature study that reviews several papers in studying the advantages of the Jeopardy game. This study intended at analyzing the use of the Jeopardy game in improving students’ reading skills. The Jeopardy game helps students to read a lot and feel relaxed while learning reading. This game also fulfills five game design criteria, namely fun, educational, promoting English, interesting, and easy to use. The findings of this study showed that the Jeopardy game can be used as a fun way to improve students’ reading skills. The Jeopardy game provides a fun and active learning environment. The findings of this study are expected to provide knowledge to teachers regarding the use of the Jeopardy game which is beneficial for teachers and students in the teaching and learning process of reading.